Student Worksheet Model Learning Cycle 7E to Practice 4C Skills Learners - Mumtaza, Nazifa; Agustinaningsih, Wiwik (Jurnal Pendidikan MIPA, 2023)
Abstract: Students' 4C skills cannot be trained properly because there are no 7E learning cycle model worksheets available on temperature and heat. So students still have difficulty understanding abstract concepts in the material. The aim of this research is to determine students' 4C skills after using the 7E learning cycle model worksheet. The development method used is Research and Development (R&D) with a 4D model (define, design, develop and disseminate). The participants in this research consisted of 2 physics education lecturers and 1 psychology lecturer as validators, as well as 30 class XI MIPA students at MAN 3 Amuntai. The instruments of this research are validity questionnaires, pretest-posttest questions, communication and collaboration self-assessment sheets, and creative thinking observation sheets. 4C skills after using the 7E learning cycle model worksheet, namely critical skills obtained N-gain, namely 0.54% in the "medium" category, creative thinking skills were 60.78% at the first meeting and 62.01% at the second meeting, with the category " quite creative”, communication skills got 78.8% in the “good” category and collaboration skills got 78.2% in the “good” category. Keywords: 4C skills, learning cycle 7e, worksheet Abstrak: Keterampilan 4C peserta didik belum dapat terlatih dengan baik dikarenakan belum tersedianya lembar kerja model learning cycle 7E pada materi suhu dan kalor. Sehingga pserta didik masih kesulitan memahami konsep abstrak pada materi tersebut. Adapun tujuan penelitian ini untuk mengetahui keterampilan 4C peserta didik setelah menggunakan lembar kerja model learning cycle 7E. Metode pengembangan yang digunakan adalah Reseacrh and Development (R&D) dengan model 4D (define, design, develop dan disseminate). Partisipan penelitian ini terdiri dari 2 dosen pendidikan fisika dan 1 dosen prikologi sebagai validator, serta 30 peserta didik kelas XI MIPA di MAN 3 Amuntai. Instrumen penelitian ini yakni angket validitas, soal pretest-posttest, lembar penilaian diri komunikasi dan kolaborasi, serta lembar observas berpikir kreatif. keterampilan 4C setelah menggunakan lembar kerja model learning cycle 7E yakni keterampilan kritis memperoleh N-gain yaitu 0,54% kategori “sedang”, keterampilan berpikir kreatif sebesar 60,78% pada pertemuan pertama dan 62,01% pada pertemuan kedua, dengan kategori “cukup kreatif”, keterampilan komunikasi memperoleh 78,8% kategori “baik” dan keterampilan kolaborasi sebesar 78,2% kategori “baik”  Kata kunci: keterampilan 4c, learning cycle 7e, lembar kerja DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp846-858